IJCM_78A: Risk perception regarding Covid 19 and Hesitancy towards COVID 19 vaccine uptake among Health Science students in Mangalore - Priya Aastha; Jahanvi; Gupta Vidit; Gupta Adit; Rekha T; Jahagirdar Shubhashri; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Public perception regarding the disease and concerns regarding safety and reliability of the new COVID 19 vaccine is the determining factor for acceptance of the vaccine. Objectives: To assess the risk perception of the health science students towards COVID 19 and COVID 19 vaccination. Methodology: A total of 701 health science students from Kasturba Medical College, Mangalore and Manipal College of Dental Sciences, Mangalore were included in this cross-sectional study. Institutional Ethics Committee permission was obtained prior to the commencement of the study. Risk perception towards COVID 19 and COVID 19 vaccination was assessed using Health belief model questionnaire. Data was analysed using IBM SPSS for windows version 25.0, Armonk, New York, 25.0. Results: Among the total participants, a higher proportion (57.6%) of the participants had a strong belief that COVID 19 can cause serious infection and 75.1% had strong belief that COVID 19 vaccine could provide protection against infection. Majority, 62% of the participants had received the 1st dose of vaccine, however, 37.6% had hesitancy. Conclusion: A lower percentage of the study participants had hesitancy towards COVID 19 vaccine. Major reasons for hesitancy were fear of side effects, history of allergic reactions, concern about safety and efficacy of the vaccine.